Analisis Cara Belajar Siswa Kelas Program Khusus (PK) Pada Mata Pelajaran Matematika di Mts Muhammadiyah Tawangsari Sukoharjo - Dhea Fattikha Paradhani; Afif Afghohani; Isna Farahsanti (Universitas Veteran Bangun Nusantara, 2023)
The purpose of this study was to find out the most widely used learning method by special program (PK) students at Mts Muhammadiyah Tawangsari and the results of this study are expected to be used as a source of other research. The research method uses qualitative methods with descriptive analysis strategies. The research time is from May – August 2022, the location is at Mts Muhammadiyah Tawangsari with the subject of class IX PK students totaling 28 students. Data collection by triangulation method, namely observation, questionnaires and interviews. Observations were made to determine indicators of student learning, the questionnaire contained 20 statements according to the indicators of learning methods that had been validated by the validator lecturer, and interviews related to learning indicators to strengthen answers from the questionnaire. The results of the questionnaire analysis of 5 indicators, namely the indicator of managing study time got a percentage of 55%, the indicator of repeating the lesson got a percentage of 49%, the concentration indicator got 67%, the indicator of making and reading notes got a percentage of 69%, and the indicator doing assignments got a percentage of 58%. The results of the study can be concluded that the learning method that gets the highest percentage is taking notes and reading notes with a percentage of 69%. Learning how to take notes and read notes is the most frequently used learning method by class VIII Special Program students at Mts Muhammadiyah Tawangsari. Tujuan penelitian ini adalah untuk mengetahui cara belajar yang paling banyak digunakan oleh siswa kelas program khusus (PK) di Mts Muhammadiyah Tawangsari dan hasil penelitian ini diharapkan dapat dijadikan sebagai salah satu sumber penelitian yang lain.Metode penelitian menggunakan metode kualitatif dengan strategi analisis deskriptif. Waktu penelitian dari bulan Mei – Agustus 2022, lokasi di Mts Muhammadiyah Tawangsari dengan subjek siswa kelas IX PK yang berjumlah 28 siswa. Pengumpulan data dengan metode triangulasi yaitu observasi, angket dan wawancara. Observasi dilakukan untuk menentukan indikator cara belajar siswa, angket berisi 20 butir pernyataan sesuai dengan indikator cara belajar yang telah divalidasi oleh dosen validator, dan wawancara berkaitan dengan indikator cara belajar untuk memperkuat jawaban dari angket.Hasil analisis angket dari 5 indikator yaitu indikator mengatur waktu belajar memperoleh persentase 55%, indikator mengulangi pelajaran memperoleh persentase 49%, indikator konsentrasi memperoleh 67%, indikator membuat dan membaca catatan memperoleh persentase sebesar 69%, dan indikator mengerjakan tugas memperoleh persentase 58%.Hasil penelitian dapat disimpulkan cara belajar yang mendapat persentase paling tinggi yaitu mencatat dan membaca catatan dengan persentase 69%. Cara belajar mencatat dan membaca catatan merupakan cara belajar yang paling sering digunakan oleh siswa kelas IX Program Khusus di Mts Muhammadiyah Tawangsari.